The Role of Cambridge Curriculum in Shaping Academic Achievement in Sekolah Putri Darul Istiqamah - Safruddin, Nikmawati; Dollah, Syarifuddin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Education plays a pivotal role in shaping the intellectual, emotional, and social development of students. In the era of globalization, where critical thinking, problem-solving, and communication skills are highly valued, curriculum selection significantly influences academic performance. This study investigates the impact of the Cambridge curriculum on students' academic achievement at Sekolah Putri Darul Istiqamah, a school committed to nurturing excellence among young women by combining high-quality education with Islamic values. The Cambridge curriculum, developed by Cambridge Assessment International Education, is recognized globally for its rigorous academic standards, emphasis on analytical thinking, and holistic approach to education. At Sekolah Putri Darul Istiqamah, its implementation has enhanced academic performance, developed essential skills, and aligned seamlessly with the institution’s mission of integrating global academic excellence with Islamic teachings. This study employs qualitative descriptive-exploratory methods, including interviews, focus group discussions, and classroom observations, to analyze the curriculum’s effectiveness. The findings highlight significant improvements in students’ academic performance, critical thinking, and communication skills while ensuring alignment with moral and cultural values. Challenges such as resource allocation and initial adaptation were also identified but were mitigated through collaborative efforts. The study concludes that the Cambridge curriculum provides a balanced approach, enabling students to achieve global competency while staying connected to their cultural and religious identity.